2022
DOI: 10.1007/s00213-022-06175-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-administered methamphetamine on GABAergic interneuron populations and functional connectivity of the nucleus accumbens and prefrontal cortex

Abstract: Introduction Methamphetamine (METH, “ice”) is a potent and addictive psychostimulant. Abuse of METH perturbs neurotransmitter systems and induces neurotoxicity; however, the neurobiological mechanisms which underlie addiction to METH are not fully understood, limiting the efficacy of available treatments. Here we investigate METH-induced changes to neuronal nitric oxide synthase (nNOS), parvalbumin and calretinin-expressing GABAergic interneuron populations within the nucleus accumbens (NAc), pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…These changes to PV neuronal function may not consistently result in changes to the number or density of PV neurons as results in adult males vary [7,55,56].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These changes to PV neuronal function may not consistently result in changes to the number or density of PV neurons as results in adult males vary [7,55,56].…”
Section: Discussionmentioning
confidence: 98%
“…Studies in adult males have shown modifications to inhibitory neurotransmission during exposure to amphetamines [5,53] and long-term modifications to inhibitory neurotransmission after adolescent stimulant exposure [8,40,54], but females were not examined. These changes to PV neuronal function may not consistently result in changes to the number or density of PV neurons as results in adult males vary [7,55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to magnetic resonance spectroscopy, a reduction in N-acetylaspartate (NAA) was discovered within the basal ganglia, frontal lobe, and anterior cingulate, indicating a reduction in neuronal integrity in these zones (80,81,82). Alteration of GABA function following addiction may be the result of multiple factors, including alterations in neuronal firing or synaptic connectivity (83).…”
Section: Discussionmentioning
confidence: 99%